Will ASEAN be successful in its quest for regional digital transformation, specifically, in the formulation of a regional rules-based digital order for cyberspace? Why? Or Why not? - Razana Binte Mohamed Rafi (Nanyang Technological University, 2023)
Great power competition between China and the United States will continue unabated, especially in the realm of technology concerning digital transformation and the evolving cyberspace. With great powers fighting, one may rightfully wonder where does the Association of Southeast Asian Nations (ASEAN), a regional organisation made up of ten Southeast Asian countries, come into play? This study argued that ASEAN, despite its size and apparent gridlock, does have a say in shaping the new order. This study endeavoured to understand if ASEAN can be successful in its quest for regional digital transformation, specifically, in the formulation of a regional rules-based digital order for cyberspace. This study discovered that ASEAN’s actorness on the issue of digitalization is moderate and in order to effectively achieve what it has set out to do, more needs to be done.